Long Relationship of Suffering with Depression in Patients with Type 2 Diabetes Mellitus at Limboto Health Center - Anggy Nurmanifa Humagi; Siti Rahma; Mihrawaty S. Antu (Universitas Muhammadiyah Palu, 2026)
Type 2 diabetes mellitus is a chronic disease that continues to increase and requires long-term management because it can cause various complications, including psychological disorders such as depression. Long suffering from the disease is one of the factors that can affect the patient's psychological condition. This study aims to analyze the relationship between the length of suffering and the incidence of depression in patients with type 2 diabetes mellitus at the Limboto Health Center. The method of this study is quantitative with a correlational analytical design through a cross sectional approach. The population is all patients with type 2 diabetes mellitus which totals 1002 people, and a sample of 91 respondents with purposive sampling techniques. The instrument of this research is the Beck Depression Inventory (BDI-II) questionnaire. The data was analyzed using the Spearman Rank Test. The results showed that the length of suffering was the most <5 years (54.9%) and the incidence of depression in patients with type 2 diabetes mellitus was categorized as minimal, so there was no relationship between the length of suffering and the incidence of depression. This research is expected to improve health services for patients with type 2 diabetes mellitus by conducting routine monitoring or screening, not only the physical condition but also the psychological condition of the patient.